عبد القادر عبد الله عباس ناسوتيون وإسهاماته في التفسير بالملايوية دراسة وتحليل - Abdul Kadir, M. N.; Ibrahim, M. (Universiti Sains Islam Malaysia, 2024)
Haji 'Abdullah bin 'Abbas Nasution was a prominent Malay scholar. Regardless, he was not known by many although he was an active scholar in various fields of life such as author, translator, teacher and polotician. Haji 'Abdullah bin 'Abbas Nasution has also produced works such as "The Quran in Jawi for children's daily recitation" and "Daily Translation of al-Quran al-Karim". He was one of the individual's who have passion in improving the Malays in Malaysia and their competence in understanding and comprehending all sciences and not only religion. He also believed that the Malays should develop themselves and forge a strong link with Allah even after obtaining their independence from the colonial power. This message is apparent from his endless struggles and sacrifices, which are also reflected in his works. This article focuses on his "Daily Translation of the Quran". Throughout this book, he clarified the importance of referring to Allah's book, contemplatng, implementing and regarding it as a system of life, and not merely for devotion. In fact, it guides people in all aspects of life; including marriage, transactions, crimes, and so on.